Model for the Formation of Professional Competence of Bachelors in the Field of Service with the Help Of 3D Technology and Graphic Visualization (Eurasian Scientific Herald, 2022)
This article addresses the analysis of the model phenomenon in pedagogical research. According to the definitions given in some dictionaries and reference books, the understanding of the model as the mavhum image of some seemingly reality is noted.